Study of inertial hydrodynamic focusing in sheath-driven flows for lab-on-a-chip flow cytometry - Panwar, Nishtha (2019)
Miniature flow cytometer models enable fast and cost-effective management of diseases in vulnerable and low-end settings. The single-line focusing of cell or particle samples is achieved using hydrodynamic forces in the microfluidic channels. The two common configurations among them are the single-sheath and dual-sheath flows wherein the sample is directed through the main channel, and the surrounding sheath fluids are directed into the main channel through inlets on either side of the main channel. Most models predict the width of the focused sample stream based on hydrodynamic focusing in the low Reynolds number regime (Re << 1), where the viscous forces dominate the inertial forces. In this work, we present comparative analysis of particle focusing by single-sheath and dual-sheath configurations for focusing of micron-sized cells/particles in the range 2 to 20 μm in the higher Re (10 < Re < 80) laminar regime. A quantitative analysis of the relative focused stream width (wf/wch) as a function of flow rate ratio (FRR = Sample flow rate/Sheath flow rate) for the two configurations is presented. The particle tracing results are also compared with the experimental fluorescent microscopy results at various FRR. The deviations of the results from the theoretical predictions of hydrodynamic focusing at Re << 1, are explained analytically. These findings clearly outline the range of flow parameters and relative particle sizes that can be used for cytometry studies for a given channel geometry. This is a highly predictive modeling method as it provides substantial results of particle positions across the microchannel width according to their size and FRR for single-line focusing of particles. Such information is crucial for one to engineer miniaturized flow cytometry for screening of desired cells or particles.